Education and Income Dynamics in Urban and Regional Labour Market Mobility - Lasse Sigbjorn Stambol (European Regional Science Association (ERSA), 2006)
Well-functioning local labour markets are expected to become net receivers of labour from other regions. In addition these regions are also expected to attract the most qualified labour and thus be the winners in the competition for the best human capital. For an examination of the two concepts "brain-gain" (a relative gain of qualified persons) and "brain-drain" (a relative loss of qualified persons), we do introduce a concept of average education based on the number of years each person have been in education altogether. There are thus reasons to expect that the regions with the highest net in-migration to job also benefit from a "brain-gain" through the migration process and vice-versa that regions experiencing a strong net loss through the migration process also suffer from a "brain-drain" in this respect. Some regions may, however, compensate a negative net-migration with a "brain-gain" through the migration process, whilst some regions may experience a "brain-drain" through migration in spite of positive net in-migration. The "brain-gain", "brain-drain" approach poses also important questions in terms of intra- and interregional competitiveness of human capital across the different industrial sectors, which is also taken into consideration in the analysis. We have as well put forward hypotheses expecting that employed persons that add to their highest formal education another year of formal education will also raise their income above the average increase of income. On the other hand the most qualified labour expects to achieve as much return on their human capital investment as possible, pushing their careers in direction of those regions and those sectors of the economy that actually give the best return. The final section of the paper is thus stressing two main aspects of these topics, first analysing the relative rise of income among employed persons changing their educational level, and second analysing the return to human capital by help of changes in personal income in different person groups by industrial sectors and regional typologies.
Keywords: 330